Using a Spatial Analysis Method to Study the Seismo-Ionospheric Disturbances of Electron Density Observed by China Seismo-Electromagnetic Satellite - Liu, Jing; Qiao, Xiaoling; Zhang, Xuemin; Wang, Zhuangkai; Zhou, Chen; Zhang, Yu (Frontiers in Earth Science, 2022)
Due to the complex processes of earthquake preparation, the observations and studies associated with earthquakes have attracted the attention of geophysicists for many years. The CSES was successfully launched on February 2, 2018. This satellite can provide global data of the electromagnetic field, plasma and energetic particles in the ionosphere to monitor and study the ionospheric perturbations associated with earthquakes. Focus on the characteristics of CSES, a spatial analysis method was proposed to extract the disturbances of electron density prior to earthquakes. Taking Indonesia Mw6.9 earthquake occurred on August 5, 2018 as an example, the spatial method was illustrated and verified by another analysis method also using the data of electron density and GPS TEC data with the same analysis method. Based on the electron density of CSES during more than two years, this method was applied to carry out the statistical study prior to Mw≥6.0 global earthquakes by Superposed Epoch and Space Approach (SESA) method. It was found that: 1) relative to the epicenters, seismo-ionospheric disturbances are more obvious in the equator direction than those in the polar direction; 2) the anomalies within 300 km distance from the epicenter are significant 11, 3 and 2 days prior to Mw≥6.0 earthquakes; 3) the influence region of perturbances associated with earthquakes is enlarging with the magnitude increasing, and the stronger magnitude is the earlier disturbance appears. These statistical characteristics were not detected for the random earthquakes. Comparing the statistical result with the simulation output, the electric field pathway could be considered as the main channel of lithosphere-atmosphere-ionosphere coupling.